Assessment of the Chemical Profile and Potential Medical Effects of a Flavonoid-Rich Extract of Eclipta prostrata L. Collected in the Central Highlands of Vietnam - Thi Kim Phung Phan; San-Lang Wang; Quang Vinh Nguyen; Tu Quy Phan; Tan Thanh Nguyen; Thanh Tam Toan Tran; Anh Dzung Nguyen; Van Bon Nguyen; Manh Dung Doan (MDPI AG, 2023)
Eclipta prostrata L. (EPL), a medicinal plant, is widely utilized in the central highlands of Vietnam. This study aims to assess the chemical profile and potential medical effects of an EPL extract rich in flavonoids. A total of 36 secondary metabolites were identified from the EPL extract through GC-MS and UHPLC-UV analysis. Among them, 15 volatile compounds and several phenolic and flavonoid chemicals, including salicylic acid, epicatechin gallate, isovitexin, and apigetrin, were reported in EPL extract for the first time. This herbal extract demonstrated moderate inhibition against α-amylase and α-glucosidase, and high anti-oxidant and anti-acetylcholinesterase activities (IC50 = 76.8 ± 0.8 μg/mL). These promising attributes can be likely attributed to the high levels of major compounds, including wedelolactone (1), chlorogenic acid (3), epicatechin gallate (6), salicylic acid (8), isovitexin (9), apigetrin (11), and myricetin (12). These findings align with the traditional use of EPL for enhancing memory and cognitive function, as well as its potential benefits in diabetes management. The results of the molecular docking study reveal that the major identified compounds (1, 6, 9, and 11) showed a more effective acetylcholinesterase inhibitory effect than berberine chloride, with good binding energy (DS values, −12.3 to −14.3 kcal/mol) and acceptable values of RMSD (1.02-1.67 Å). Additionally, almost all the identified major compounds exhibited good ADMET properties within the required limits.